IMPROVING STUDENTS’ READING SKILL BY USING SKIMMING TECHNIQUE AT THE SECOND YEAR STUDENTS OF SMA NEGERI 4 KOTA TERNATE - Ajwan Muddin; Rahmi Rahayamtel (Peneliti.net, 2018)
Student awareness of reading and thinking processes is further encouraged in many parts of the book by exercises that require them to work in pairs or small groups. In discussions with others, students formulate and articulate their ideas more precisely and thus acquire new ways of talking and thinking about a text. The researcher was going to know how well the students’ reading skills using skimming technique. This research used quantitative research with pre-experimental one group pretest and posttest designs with the sample were taken by using cluster sampling. The population of this research was 160 of the second year students at SMAN 4 Kota Ternate and total sample were the whole students of XI IPA 4, contained 38 students. However, when researcher was conducted 8 students were absent so that the total sample was 30 students. . The data was collected by giving 30 items pretest and posttest then, was analyzed by using t-test formula. The results of the data analysis showed that the mean scores of post test was ∑ = 1790 = 59.7 is higher than the mean scores of pretest was ∑= 1634 = 54.5. Statistically, the t-count was improved on 2.6 than the table was 1.699with degrees of freedom (df) 29 and level of significance at 0.05. There was difference between post test and pretest by students’ reading skill. Based on the data analysis, the null hypothesis is rejected and the alternative hypothesis accepted.